Simplified Accounting Procedures for Small-Scale Banks: Insights from Bank Sampah Cangkringan Berseri: Prosedur Akuntansi yang Disederhanakan untuk Bank Skala Kecil: Wawasan dari Bank Sampah Cangkringan Berseri - Rahmawati, Fauziah; Nurasik (Universitas Muhammadiyah Sidoarjo, 2023)
This research aimed to investigate the accounting process used at Bank Sampah Cangkringan Berseri, Kec. Sukodono, Kab. Sidoarjo, Indonesia, from transaction analysis to financial report preparation. The data collection process involved triangulation techniques, including interviews, observation, and documentation. The data were analyzed for validity, reduced, classified, and presented. The findings indicated that Bank Sampah Cangkringan Berseri did not take a profit-sharing approach but instead took the difference between the selling price to collectors. The accounting records were kept in simple formats to facilitate easy understanding by other administrators. The research revealed that the bank only used a few accounting stages, including transaction analysis, original evidence collection, journal entry recording, ledger recording, and financial reporting. This simplified process was due to the bank's small scale, which did not require a balance sheet, adjusting journal entries, and a trial balance. The implication of the research is that small-scale banks can adopt simplified accounting procedures to reduce operational complexity and costs. Highlights: Bank Sampah Cangkringan Berseri did not take a profit-sharing approach but instead took the difference between the selling price to collectors. The research revealed that the bank only used a few accounting stages, including transaction analysis, original evidence collection, journal entry recording, ledger recording, and financial reporting. This simplified process was due to the bank's small scale, which did not require a balance sheet, adjusting journal entries, and a trial balance. The implication of the research is that small-scale banks can adopt simplified accounting procedures to reduce operational complexity and costs.